Money from Islamic perspective: its purpose and time value - Abdul Aziz, Akhtarzaitie (IIUM Institute of Islamic Banking and Finance, 2009)
Money from Islamic commercial law perspective is essentially a medium of exchange and not an ordinary commodity that can be freely traded for profit. This paper will explore the nature of money in Islamic law and its function. A number of guiding principles in dealing with money will be discussed. Next the paper will also examine one of very important issues in current Islamic transaction which is the issue of the time value of money. The main issue is whether in Islam, where money is not a commodity which can be traded freely at any price, necessarily means that there is no weight or value to be given to time factor in economic and financial transactions. Does time value of money means the adoption of Riba as it is practiced by the conventional banking transaction ? An important issue which arises in the case of sale based financing and it's pricing whereby price to be paid in future is higher than spot price relates to the issue of positive time preference of money. This paper shows that Islam differentiates between cash advance on interest and commodity sold on mark-up basis, particularly Murabahah though both involve time element and positive time preference of money.